Electroreductive Decomplexation and Isomerism of Copper(II) Complexes with Cyclam Ligands for Medical Use - Koláčná, Lucie; Maďar, Milan; Kubíček, Vojtěch; Ludvík, Jiří (ChemElectroChem, 2024)
Detailed electrochemical study of copper(II) complexes of cyclam bearing two phosphonate (TE2P), phenolate (TE2PhOH) or carboxylate (TE2A) pendant arms (together with one cross‐bridged‐cyclam derivative cb‐TE2A) was performed using cyclic voltammetry (CV) and polarography. The electrochemical‐heterogeneous measurements were accompanied by UV‐vis spectra describing the situation in homogeneous phase. Reduction of complexes on mercury electrode in buffered aqueous solutions (pH 2–12) occurs generally as a two‐electron process of reductive decomposition. The formed Cu‐amalgam can be (e. g. during the anodic scan of CV) reoxidized to Cu(II) cation which undergoes re‐complexation resulting in the original complex. This process of a square diagram is manifold repeatable. The results also showed presence of several isomers differing in mutual orientation of substituents on cyclam nitrogen atoms. The primary “kinetic”, pentacoordinated isomers are irreversibly transformed to the stable, hexacoordinated “thermodynamic” ones upon heating. The development of isomerization process was followed electrochemically. The cross‐bridged cb‐TE2A derivative forms only one isomer which does not change even after heating. The higher stability of the complex manifests itself at pH>8 when the complex is reversibly reduced in one‐electron step, formally CuII/CuI, without decomposition. Electrochemical study of copper(II) complexes of cyclam bearing two phosphonate, phenolate or carboxylate pendant arms in buffered solutions using mercury electrodes is presented. Two‐electron irreversible reductive decomplexation yields Cu‐amalgam which is during the anodic scan of CV reoxidized to Cu(II). The latter undergoes re‐complexation resulting in the original complex. Several isomers are electrochemically identified and their thermal transformations described.